Comparison of condylar and ramal asymmetries in different temporomandibular joint disorders (Annals of Medical Research, 2021)
Aim: The aim of this study is to compare condylar and ramal asymmetries in different temporomandibular joint disorders.Material and Methods: A total of 91 patients ranging in age from 15 to 79 were included in this study. The study groups were as follows: temporomandibular joint osteoarthritis (OA) group (N=24), disc displacement with reduction (DDWR) group (N=26), disc displacement without reduction (DDWoR) group (N=20), and control group (N=21). All patients’ vertical condylar and ramal heights were measured from panoramic radiographs, and condylar (CAI) ramal (RAI), and total (TAI; condylar + ramal) asymmetry indices were calculated according to Habets el al’s formula.Results: Statistical evaluations were made with the Kruskal–Wallis test using SPSS. Although TAI (p=0.110) and age (p = 0.610) did not differ significantly among the four groups, RAI (p=0.003) and CAI (p = 0.034) did. In intergroup estimates for RAI comparisons, significant differences were observed between the OA and DDWR groups (p=0.004, p=0.033) and between the OA and control groups (p=0.033). Evaluations of CAI among groups showed significant differences only for the OA vs. control group comparison (p=0.022). Conclusion: These results show that OA, a degenerative disease, has greater effects on vertical condylar and ramal asymmetry than on disc displacements and that there are no significant differences between the control and disc displacement groups in terms of CAI.
Keywords: Condylar asymmetry; ramal asymmetry; temporomandibular joint disorders